Upper-ocean structure variability in the Northwest Pacific Ocean in response to tropical cyclones - Yu, Jie; Zhang, Han; Wang, Huizan; Tian, Di; Li, Jiagen (Frontiers in Marine Science, 2023)
The upper ocean structure obviously affects sea surface temperature cooling (SSTC) induced by tropical cyclones (TCs). Herein, principal component analysis of many Argo profiles from 2001 to 2017 in the Northwest Pacific Ocean is used to classify the upper ocean structure. The results suggest that the upper ocean structure can be divided into four types of water. Water with low mode 1 scores (M1-L water) is characterized by an extremely warm sea surface temperature (SST), while a cold and thick isothermal layer is observed for water with high mode 1 scores (M1-H water). Water with high mode 2 scores (M2-H water) has a warm SST and a thick isothermal layer. Relative to M2-H water, water with high mode 3 scores (M3-H water) has a warmer SST but a shallower mixed layer. These waters have remarkable seasonal and spatial variability, mainly associated with the impacts of solar radiation, precipitation, currents and mesoscale eddies. The ocean responses to TCs are different among these water types, which greatly influences the TCs intensification. The response of M1-H water is not considered, since its SST is below 26°C. The TC-induced SSTC of M3-H water (-1.12°C) is markedly higher than that of M1-L (-0.68°C) and M2-H waters (-0.41°C). Moreover, the one-dimensional mixed layer model shows a much smaller entrainment rate for M2-H water due to its thick barrier layer. The number of each water type changes in association with global warming and Kuroshio path, and thus affects the TC intensification.